Phytoconstituent Analysis of Cocculus hirsutus L. by GC-MS, FT-IR, and UV-VIS - R. Manonmani; M. Jayapriya; G. Soshina Iswarya (International Journal of Pharma and Bio Sciences, 2024)
There is a growing interest in the chemical composition of plant-based medicines. Bioactive constituents have been isolated and studied for pharmacological activities. Plant-based drugs remain an important source of therapeutic agents because of their availability, relatively cheaper cost, and non-toxic nature compared to modern medicine. Cocculus hirsutus L., locally called Jaljamini, belongs to Menispermaceae and is a climbing scandent shrub with hairy sepals. The leaves of C. hirsutus L. were screened to identify and analyze the phytochemical constituents responsible for developing new drugs. The preliminary phytochemical analysis showed the presence of major phytoconstituents like alkaloids, phenolic compounds, flavonoids, etc. The studies on the bioactive components in the methanolic seed extract of C. hirsutus L. by GC-MS analysis showed the presence of four bioactive compounds such as 2-hexyldecanoic acid (220.19%), 2-Hydroxy–14–methyl– oxa – cyclotetradec – 6 – en – 2 – one (122.04%), 11-Hexadecyn –1–ol (622.56%), 6, 9 - octadecadienoic acid methyl ester (226.27%). The infrared spectrum analysis of methanolic and aqueous seed extracts of C. hirsutus L. showed the presence of alkyl halide, alcohol, aromatic, acid, and alkyne functional groups. The UV-VIS spectrum analysis results of methanolic and aqueous seed extract of C. hirsutus L. showed absorption at 311 nm (-0.403) and 310 (-0.110), respectively. The results obtained in our study suggest that, the leaf extract of Cocculus hirsutus L. can be a promising candidate for the development of phytomedicine in the treatment and prevention of various ailments.